Consumer Behaviour of small Car Owners -A Factor Analytic Approach - Narayanan, KG (Gyan Management Journal, 2007)
Liberalization of Indian economy follO\wd by the de-licensing of the passenger car industry has led to the launch of a number of new brands in the Indian market that has triggered the bigge t ever battle for market share. t has re-written the rules of the game of the Indian automobile industry. The demand for small cars is growing at a very fast rate. With the arrival of multinationals bringing in quality products, a cut-throat competition has emerged in the car market. Since 1991, the scenario in the passenger car
Keywords: Liberalization; Indian economy; passenger car industry; monopolistic